Large‐scale lateral saturated soil hydraulic conductivity as a metric for the connectivity of subsurface flow paths at hillslope scale. Issue 8 (7th August 2022) - Pirastru, Mario; Iovino, Massimo; Marrosu, Roberto; Di Prima, Simone; Giadrossich, Filippo; Awada, Hassan
Abstract: Lateral saturated soil hydraulic conductivity, K s, l, is the soil property governing subsurface water transfer in hillslopes, and the key parameter in many numerical models simulating hydrological processes at the hillslope and catchment scales. Likewise, the hydrological connectivity of the lateral flow paths plays a significant role in determining the rate of the subsurface flow at various spatial scales. This study investigates the relationship between K s, l and hydrological connectivity at the hillslope spatial scale. K s, l was determined by the subsurface flow rates intercepted by drains and water table depths observed in a well network. The hydrological connectivity was evaluated by the synchronicity among water table peaks, and between these and the peaks of the drained flow. Rainfall and soil moisture were used to investigate the influence of the transient hydrological soil condition on connectivity and K s, l . As the synchronicity of the water table response between wells increased, the lag times between the peaks of water levels and those of the drained subsurface flow decreased. Moreover, the most synchronic water table rises determined the highest drainage rates. The relationships between K s, l and water table depths were highly non‐linear, with a sharp increase in the values for water table levels close to the soil surface. Estimated K s, l values for the full saturated soil were in the order of thousands of mm h −1, suggesting the activation of macropores in the root zone. The K s, l values determined at the peak of the drainage events were correlated with the indicators of synchronicity. The sum of cumulative rainfall and antecedent soil moisture was correlated with the connectivity indicators and K s, l . We suggest that, for simulating realistic processes at the hillslope scale, the hydrological connectivity could be implicitly considered in hydrological modelling through an evaluation of K s, l at the same spatial scale. Abstract : The lag times between the peaks of water levels and of the drained subsurface flow decreased as the synchronicity between wells increased. The K s, l values determined at the peak of the drainage events were correlated with the indicators of synchronicity. The sum of cumulative rainfall and antecedent soil moisture was correlated with the connectivity indicators and K s, l .